(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This practical studying involved preparation and development of new medical derivatives of ciprofloxacin drug via series of chemical reactions to preparation new derivatives to resist types of bacteria in hospitals and environment.Various chemical routes have been used to prepare ciprofloxacin derivatives ,then all these derivatives reconnoitered with many spectral chemical techniques for instance (FT.IR ,H.NMR ,C.NMR )– spectrophotometric ,then studying of their effects on bacterial pollution.